2015
DOI: 10.1017/s0029665115003328
|View full text |Cite
|
Sign up to set email alerts
|

Optimising pre-load study design for satiety assessment

Abstract: Laboratory-based pre-load studies are often used to quantify the effects of foods and/or food ingredients on satiety and satiation. Important considerations when designing pre-load studies include, but are not limited to, the timings of the study meals in relation to habitual intake, the duration between the pre-load and ad libitum test meal, and the nutrient content and palatability of the study meals provided (1) . We conducted a pilot study to determine the satiety effects of, i) a gender-specific compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Modification of gut microbiota included an increase in Bacteroides spp, a decrease in Clostridium perfringens and the production of several SCFAs. In other studies performed on either animal models, healthy volunteers or specific human populations (diabetic women), RD showed different beneficial health responses, such as antiobesogenic, [21][22][23][24][25][26] cholesterol-lowering, [27] anti-inflammatory, [28][29][30] or positive influence on the immune system response. [29] Most of the interventional (human) studies with fibers focused on specific taxa, targeting only Bifidobacterium and Lactobacillus, thus following the first prebiotic definition.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of gut microbiota included an increase in Bacteroides spp, a decrease in Clostridium perfringens and the production of several SCFAs. In other studies performed on either animal models, healthy volunteers or specific human populations (diabetic women), RD showed different beneficial health responses, such as antiobesogenic, [21][22][23][24][25][26] cholesterol-lowering, [27] anti-inflammatory, [28][29][30] or positive influence on the immune system response. [29] Most of the interventional (human) studies with fibers focused on specific taxa, targeting only Bifidobacterium and Lactobacillus, thus following the first prebiotic definition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that resistant dextrin has the effect of reducing blood cholesterol and antiobesity. [7][8][9] Liu et al found that supplementation of resistant dextrin can inhibit lipogenic enzyme activity and induce fatty acid (FA) 𝛽-oxidation by increasing AMP kinase activation, thereby reducing lipid accumulation in the liver. [10] The high-amylose corn starch selected in this study had high-amylose content and low glycemic index (GI), and it was proved to reduce the weight gain, liver lipid accumulation, and adipocyte hypertrophy induced by high-fat diet, and to improve blood lipid profile.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that resistant dextrin has the effect of reducing blood cholesterol and antiobesity. [ 7–9 ] Liu et al. found that supplementation of resistant dextrin can inhibit lipogenic enzyme activity and induce fatty acid (FA) β‐oxidation by increasing AMP kinase activation, thereby reducing lipid accumulation in the liver.…”
Section: Introductionmentioning
confidence: 99%